Experimentation and optimization of phase change material integrated passive bifacial photovoltaic thermal greenhouse dryer - Sehrawat, Ravin; Sahdev, Ravinder Kumar; Chhabra, Deepak; Tiwari, Sumit (Solar energy, 2023)
•Bifacial PVT Greenhouse dryer with PCM is designed and developed.•The operating hours and performance of the dryer with PCM are improved.•North wall insulation with aluminium foil is used for better performance.•MOGA-ANN methods have been used to explore the performance of PVT dryer. A greenhouse dryer is the most economical and environmentally friendly device used to dry various products like fruits, vegetables and meats. The operating hours and heat losses from the north wall are the main concerns for its performance. To minimize the heat losses and improve the operating hours, the present study is undertaken on a modified hybrid greenhouse dryer with a thermal energy storage system and a bifacial photovoltaic thermal for electrical (BIFPVT) and thermal energy. A thermocol was wrapped in an aluminium foil (As a reflector) and placed on the north wall to minimize energy losses. The integration of PCM made the system sustainable to use while off sunshine hours as it stores the thermal energy during daytime. It was observed that the BIFPVT system provided electrical power ranging from 2.0 to 85.5 W and 0.6–81 W with respect to solar radiation intensity on the front (IF) and rear (IR) side of BIFPVT which varied from 34–950 W/m2 and 13–350 W/m2, respectively. The drying room temperature was found to be 16–44% higher than the ambient temperature for both days. Further, the experiment result was trained using an artificial neural network and optimized with the help of multi-objective genetic algorithm tools.